2019
DOI: 10.1111/ijd.14590
|View full text |Cite
|
Sign up to set email alerts
|

Dermoscopy of primary cutaneous B‐ and T‐cell lymphomas and pseudolymphomas presenting as solitary nodules and tumors: a case‐control study with histopathologic correlation

Abstract: Background Primary cutaneous lymphomas (PCLs) and pseudolymphomas presenting as single pink-red nodules/tumors are highly unspecific and include a wide differential diagnosis.Objective To describe the dermoscopic characteristics of PCL/pseudolymphoma. MethodsIn this retrospective, case-control study, we evaluated the dermoscopic features of patients with solitary PCL/pseudolymphoma tumors and compared them to a control group of non-lymphomatous, nonpigmented, solitary tumors (e.g., basal cell carcinoma, amelan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 23 publications
1
10
0
1
Order By: Relevance
“…While in our study we were not able to correlate it with a certain histologic alteration, it has been described in the literature that dense monomorphous lymphocytic infiltrate may result in faint orange color in dermatoscopy. This finding has been reported only in patients with lymphoma and pseudo lymphoma, and not in patients with CLE so far 14 …”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…While in our study we were not able to correlate it with a certain histologic alteration, it has been described in the literature that dense monomorphous lymphocytic infiltrate may result in faint orange color in dermatoscopy. This finding has been reported only in patients with lymphoma and pseudo lymphoma, and not in patients with CLE so far 14 …”
Section: Discussionmentioning
confidence: 57%
“…This finding has been reported only in patients with lymphoma and pseudo lymphoma, and not in patients with CLE so far. 14 Lallas et al reported a significant correlation between gray color in dermatoscopy and the presence of melanophages in histology. 6 Gray color as a dermatoscopic feature was not represented in a high In our study, there was a significant overlap in the dermatoscopic features observed within the three groups.…”
Section: Resultsmentioning
confidence: 98%
“…Although direct dermoscopic–histopathological correlation of these structures has not been poorly investigated, the presence of salmon‐coloured background may correlate with atypical lymphocytic infiltrate within the dermis associated with neoangiogenesis. White structures could be associated either with reactive fibrosis in the dermis or with focally reduced grenz zone due to patchy, nodular, more superficial infiltrate in the papillary dermis 46,49 …”
Section: Resultsmentioning
confidence: 99%
“…Un aspecto importante en estos padecimientos es el diagnóstico, que en la mayoría de los casos no se realiza de forma temprana debido a las manifestaciones que se confunden con padecimientos de comportamiento benigno. Es necesario referir a los pacientes con manifestaciones clínicas de sospecha al dermatólogo, para que se realice una evaluación minuciosa, incluyendo una dermatoscopia, en busca de características orientadoras del diagnóstico de LC, como son las áreas bien organizadas con fondo color salmón, vasos serpiginosos y tapones foliculares 11 .…”
Section: Discussionunclassified